”Mawah” Profit Sharing System with Local Acehnese Wisdom Based on Islamic Perpective - Muhammad Ali; Mahadi Bahtera; Mustakim Sagita; Ayu Andira; Ziatul Via (Journal of Law, Politic and Humanities, 2024)
Aceh is an Indonesian province characterized by a predominantly Muslim population. Hence, the Islamic comprehension of economic principles, fairness, and profit-sharing systems has significant consequences for the economic progress of the Acehnese population. Research on the use of Islamic tenets in cattle farming companies may significantly benefit the welfare of the Acehnese people in this particular setting. Mawah is a commercial practice rooted in traditional conventions and local village knowledge. It involves verbal agreements between cattle owners and keepers for profit-sharing in cow husbandry. This research examines the "Mawah" profit-sharing mechanism in cattle farming firms in Pidie Regency from an Islamic viewpoint. This is an empirical investigation conducted in a natural setting. The primary issues are: 1). What is the societal impact of implementing a profit-sharing system in cattle farming businesses? 2). What is the assessment of the Islamic Economic Review about the profit-sharing model in cattle farming firms in Pidie Regency? The study used a descriptive qualitative research approach, using data gathering methods such as observation, interviews, and recording. The strategies used for data analysis include data reduction, data presentation, and data verification.